MULTILINGUALISM APPLIED IN ILP ENGLISH BOOK - Agnes Widyaningrum (Dinamika Bahasa dan Budaya, 2013)
People who can speak more than one language is called bilingual and those who canspeak more than two is called multilingual people. As a result, they can masterthe language in the form of spoken and written. The student’s books of ILPEnglish Program are also written in English. This study is aimed at finding outthe multilingual characters and multicultural elements applied in ILP student’sbooks for first graders of SD PL ST YUSUP Semarang. This documentary study is analyzed in qualitative nature by giving detailedexplanation for data. The step to collect the data is reading the books and thesteps to analyze the data are identification, classification andinterpretation. The result shows that there are some characters whose refer totheir country like Maalik represents Malaysia, Bunga represents Indonesia andalso others while the multicultural elements are expressions, physicalcharacteristics, and situation such as Hello, what’s your name?, Nice to meetyou, etc. The result shows that there are some characters that we can identiyfrom the names, and some elements behind certain condition like the expressionsused in asking and aswering.Keywords : multilingual, multicultural